The relationship between stress and employee’s turnover intention at Orang Kampung Group, Serkam Melaka / Muhammad Sazrin Ramlan - Ramlan, Muhammad Sazrin (Faculty of Business and Management, 2019)
Stress is your body’s way of responding to any kind of demand or threat. It is responses when the trying to protecting you, stress may act as mechanism that alert the body that the situation not like usual pace and the body start felt uncomfortable with it. Stress isn’t always bad, in small doses, it can help you perform under pressure and motivate you to do your best. It will rise you up to meet challenges, it is what keep you on your toes during presentation at work, sharpen the concentrations and drive person to perform the job rather than surfing the social media. But when you’re constantly running in emergency mode, your mind and your body will pay the price. This research is a quantitative research which had used the self-administered electronic questionnaire as the instrument for the collection of data. The data was collected and achieved a percentage of 80.95 out of possible 103 respondent, which was derived from the total population of 140 employee who work at Orang Kampung Group. The sampling frame for this study had been derived from employee in the manufacturing industries located at Halal-Hub Serkam, and those who currently working at Orang Kampung Group. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 23 Software. Using SPSS, numerous tests were converged such as reliability analysis frequency distribution, descriptive analysis, pearson’s correlation analysis, univariate linear regression and simple linear regression. The result of this research show low positive relationship between stress and employee turnover intention.